2019
DOI: 10.1002/jsfa.10170
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritin elicitation can increase the content of medicinally important glucosinolates and phenolic compounds in Chinese kale plants

Abstract: BACKGROUND: Brassica oleracea var. alboglabra (Chinese kale) is an important vegetable grown in southernChina. This study was aimed at searching for environmentally friendly and affordable approaches to increase the production of medicinally relevant glucosinolates and phenolic compounds in Chinese kale plants. For this purpose, the foliar application of liquiritin at 0 (control), 250, 500 and 750 ppm was tested starting from the four-leaf stage and repeated every two weeks until plants were two months old. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…All these facts refer to the possibility that recognition of animal antigens or elicitor molecules by plants can also trigger immune responses to hinder the invasion of pathogens inside plant body. Liquiritin is a flavanone glycoside that plays a significant role in boosting the immune system of mammals (Cheel et al 2010), and in our recent research, we observed that this compound also has a beneficial effect on the growth of Chinese flowering cabbage plants (Akram et al 2020). Furthermore, we found that a foliar spray of 750 ppm liquiritin enhanced the contents of phenolics and glucosinolates in addition to acylated and glycosylated flavonoids in cabbage plants Akram et al (2020).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…All these facts refer to the possibility that recognition of animal antigens or elicitor molecules by plants can also trigger immune responses to hinder the invasion of pathogens inside plant body. Liquiritin is a flavanone glycoside that plays a significant role in boosting the immune system of mammals (Cheel et al 2010), and in our recent research, we observed that this compound also has a beneficial effect on the growth of Chinese flowering cabbage plants (Akram et al 2020). Furthermore, we found that a foliar spray of 750 ppm liquiritin enhanced the contents of phenolics and glucosinolates in addition to acylated and glycosylated flavonoids in cabbage plants Akram et al (2020).…”
Section: Introductionmentioning
confidence: 67%
“…On the basis of aforementioned similarities between animal and plant defense mechanisms and our previous findings with respect to liquiritin (Akram et al 2020), we postulated that the application of this compound might have the effect of eliciting defense responses against the cucumber mosaic virus (CMV) in Chinese flowering cabbage plants.…”
Section: Introductionmentioning
confidence: 95%
“…In the course of our study, foliar application of liquiritoside showed positive effects on the growth of Chinese flowering cabbage plants (data yet not published). Additionally, we observed that liquiritoside mitigated abiotic stress, improved biosynthesis of, glucosinolates besides, flavonoids and phenolics in treated plants (Akram et al, 2020). Yet, the application of exogenously applied liquiritoside in the mitigation of plant stress has never been inspected.…”
Section: Introductionmentioning
confidence: 75%
“…We used our recently devised method (Akram et al, 2020) for the identification and quantification of different types of glucosinolates from the leaves of Chinese flowering cabbage plants. Leaves from 10 plants were taken from each treatment and pooled together.…”
Section: Quantification Of Glucosinolate Contentmentioning
confidence: 99%
“…This crisp and hearty vegetable is often consumed raw in salads and smoothies but can also be consumed in steamed, sautéed, or cooked states. Kale originates from China and has since gained particular attention in other countries due to its constituent cancer-preventive and human-health-promoting phytochemicals (i.e., glucosinolates, carotenoids, phenols, and vitamins) [ 4 , 5 , 6 ]. Glucosinolates are amino-acid-derived, active secondary metabolites that mainly contain sulfur- and nitrogen-related compounds (i.e., β-D-thioglucose, tryptophan, phenylalanine, sulfonated oxime moiety).…”
Section: Introductionmentioning
confidence: 99%